1997
DOI: 10.1577/1548-8667(1997)009<0132:eoubro>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultraviolet-B Radiation on Fish: Histologic Comparison of a UVB-Sensitive and a UVB-Tolerant Species

Abstract: Lahontan cutthroat trout Oncorhynchus clarki henshatvi were sensitive to simulated solar ultraviolet-B radiation (UVB) and exhibited grossly visible signs of sunburn upon exposure . Razorback suckers Xyrauchen texanus, however, were tolerant to simulated solar UVB and showed no grossly visible signs of exposure . Cutthroat trout also had considerably less of an unidentified, possibly photoprotective, substance in the skin than did razorback suckers . In an attempt to char acterize the cellular response to simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…On the other hand, dab eggs and embryos are pelagic and, in the less saline Baltic Sea, due to their specific weight, they drift in deeper water layers than in the more saline North Sea where they are located closer to the water surface (Nissling et al 2002). Therefore, the early life stages of North Sea dab may be less protected from an increasing impact of UV-B radiation (due to increasing global ozone depletion), which is known to affect pigmentation in various taxonomic groups, including fish (Blazer et al 1997, Jokinen et al 2000, Alemanni et al 2003. It can therefore not be excluded that increased UV-B radia-tion is responsible for the increase in prevalence of hyperpigmentation (Noguera et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, dab eggs and embryos are pelagic and, in the less saline Baltic Sea, due to their specific weight, they drift in deeper water layers than in the more saline North Sea where they are located closer to the water surface (Nissling et al 2002). Therefore, the early life stages of North Sea dab may be less protected from an increasing impact of UV-B radiation (due to increasing global ozone depletion), which is known to affect pigmentation in various taxonomic groups, including fish (Blazer et al 1997, Jokinen et al 2000, Alemanni et al 2003. It can therefore not be excluded that increased UV-B radia-tion is responsible for the increase in prevalence of hyperpigmentation (Noguera et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct effects of exposure to UV radiation are likely minimal within the context of all the other environmental factors that cause very high levels of egg and larval mortality in marine organisms, studies have shown that UV-induced egg mortality could be as high as 32.5% for the planktonic copepod Calanus finmarchicus and considerably less (1.2%) for the Atlantic cod Gadus morhua in the waters of the estuary and Gulf of St. Lawrence, Canada (Browman et al, 2000). Other direct effects of UV exposure on fish eggs or larvae include malformation (Dong et al, 2007), retarded growth (Jokinen et al, 2008), lesion of skin, eyes, and brain (Blazer et al, 1997;McFadzen et al, 2000), and weakened immune system (Markkula et al, 2005, 2006). These pernicious effects may be higher for fish larvae that are often present in surface waters since UV-B (λ = 280-320 nm) exposure induces DNA damage in a variety of fish larvae such as Atlantic cod, northern anchovy Englausis mordax, icefish Cephalus aceratus and Japanese medaka Oryzias latipes (see Fukunishi et al, 2012 for references).…”
Section: Importance Of Light Radiation For Carotenoid Production and mentioning
confidence: 99%
“…For fishes, sunburn can be fatal, but different fish species (and even strains within a species) are differentially tolerant of UV exposure (Blazer et al 1997, Armstrong et al 2002. The epithelial mucus of coral reef fishes (n = 138 species) contains varying amounts of several 'sunscreen' compounds that absorb both UVB and UVA (320 to 400 nm) radiation (Zamzow & Losey 2002, J. P. Zamzow unpubl.).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%